MUSICAL PIETY: REPRESENTATION OF ISLAM IN SOUTHEAST ASIA’S NASYID BOY-BAND MUSIC - Wati, Erna (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2015)
In recent decades, the movement of Islamisation in Malaysia and Indonesia have significantly developed. Islam in both Malaysia and Indonesia is known by its moderate character, more syncretised and politically diverse. These characteristics may have led the mass popular culture that globally spread, significantly influenced the rapid movement of Islamic popular culture in both countries. This paper analysed the rise of Islam in Malaysian and Indonesian society and politics, with a focus on Islamic popular culture. It then compared the characteristics of Malaysian Islam and Indonesian Islam movement and examine the rise of nasyid as one of Islamic popular culture products in Southeast Asia. The trends indicated that the success of popular culture adaptation such as nasyid boy-band music in Malaysia and Indonesia vary in terms of the issues that they represent. It may influenced by the economic, political and cultural agenda which involve in it.Keywords: popular culture, islamisation, islamic music, nasyid